The Youth as the Innovative Social Community - L. A. Zhuravleva; N. V. Zavyalova (Russian State Vocational Pedagogical University, 2015)
The paper looks at the contemporary youth environment from the standpoint of juvenology. The youth is regarded as a distinct social community prone to violating the norms and rules due to the specific mentality and functional characteristics. The authors denote the youth age range, social status and roles, behavior patterns, life style and subculture preferences. The youth community is most open to innovation, being its generator and consumer, conductor of information flows, initiator of new behavior patterns and stereotypes including the negative ones. The main disadvantages of the given age group are the lack of social experience, rejection of traditional cultural behavior patterns on the one hand, and high susceptibility and imitation propensity on the other hand. The research demonstrates that social deviation often results from the young people's dissatisfaction and lack of social prospects. Therefore, the factors determining the above trends are related to insufficient attention to the youth's requirements and interests on the part of the government and society.